CULTURE - FACTOR FOR ECONOMIC IMPACTS OF THE ENVIRONMENT - Popova, Daniela (E-Journal VFU, 2025)
Culture in its multifaceted nature influences all aspects of the economy and is the environment in which practically all processes that determine the market and the interactions between its individual participants take place. The aim of the paper is to highlight culture in various manifestations and as a factor in the economic environment.